Comparison of Reactive Blue 203 Dye Removal Using Ultraviolet Irradiation, Ferrate (VI) Oxidation Process and MgO Nanoparticles - Amirreza Talaiekhozani; Nilofar Torkan; Fahad Banisharif; Zeinab Eskandari; Shahabaldin Rezania; Junboum Park; Farham Aminsharei; Ali Mohammad Amani (Hamadan University of Medical Sciences, 2018)
This study investigated the effect of various parameters on the removal of Reactive Blue 203 dye from wastewater using ferrate(VI) oxidation process, ultraviolet radiation (UV) radiation and MgO nanoparticles under batch mode. Although several studies have been carried out on dye removal, there is no study on the removal of Reactive Blue 203 dye using ferrate(VI) oxidation process, UV radiation, and MgO nanoparticles. Therefore, the aim of this study is to investigate the effect of different factors including pH, temperature, contact time, the intensity of UV radiation and the concentration of MgO nanoparticles on Reactive Blue 203 dye removal using the above-mentioned methods. The results showed that the best pH values for dye removal using UV radiation, ferrate(VI), and MgO nanoparticles were 13, 1 and 13, respectively. The best temperature for Reactive Blue 203 dye removal using ferrate(VI) was 50°C. Hence, temperature variation had no significant effect on Reactive Blue 203 dye removal using UV irradiation and absorption by MgO nanoparticles. Based on the results, the best contact time was 15 minutes using UV radiation. The removal of Reactive Blue 203 dye using ferrate(VI) oxidation process was a quick reaction, and in a fraction of a second, the reactions were completed. The results showed that dye removal using MgO nanoparticles could be described by the Temkin isotherm. Therefore, the contact time was not considered as an effective parameter. In addition, the maximum dye removals were 95, 85 and 94% using UV irradiation, ferrate(VI) and MgO nanoparticles.